Visual Decision Support System Model for Managing Unemployment by Hybrid Education - Ghazali, Ahmad Faiz; Mokhtar, Nurkhairany Amyra; Suhaimi, Aishah; Mohd Yusoff, Rahmawati (Emerging Advances in Integrated Technology, 2021)
Hybrid education is an approach that helps in conducting face-to-face and online distance learning especially for formal education. However, during COVID-19 pandemic, formal education institutions including schools and universities as well as informal education through the media for communities and industries are practiced by the lawmakers to manage workplace distancing. Food supply chain are experiencing unexpected disruptions due to interrelated activities that will determine supply chain performance and efficiency. This article explores the challenges faced by food industry and related sectors due to emergence impact of COVID-19 in Malaysia. Food supply chain management (FSCM) is a complex task involving interconnected activities and numerous stakeholders for a specific food product from raw materials to final product before it reaches the end customers. An overview of COVID-19 scenarios, followed by the impact of pandemic towards the activities in food supply chain, and the management issues that need to be addressed are presented. Several challenges identified are including the worldwide implication of the pandemic scenarios to food supply chain management and food supply chain activities, and indirect impact of supply chain disruption to labour force; unemployment and retrenchment. Finally, a visual decision support system (VDSS) model is developed to illustrate the main impacts of the pandemic scenario on food supply chain as well as addressing the labour management and opportunities. It has potential to provide general guidelines to educators, policy-makers, and decision-makers  to deal with uncertainties after the pandemic